Kaidah Yang Terdapat Pada Bab Wali Nikah - Ahmad Zaky Nauval; Mhd Amar Adly; Heri Firmansyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Marriage is not only about forming a family which occurs because of the union of a man and a woman, but marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of f0orming a happy and eternal family (household) based on the belief in the Almighty God. One of the most important things about marriage is the marriage guardian. This article aims to find out the theory regarding marriage guardians, the rules for marriage guardians, the arguments and origins of the rules, examples of rules and exceptions to the rules. By using juridical-normative legal research methods, this article will review this conflict. The research results show that there are rules that regulate that a marriage guardian should not be a Fudhulli.